Once-monthly hemin suppresses inflammatory and autoreactive CD4+ T cell responses to robustly ameliorate experimental rheumatoid arthritis - Bingzhi Sun (iScience, 2021)
Summary: Rheumatoid arthritis (RA) is an inflammatory autoimmune disease that would permanently damage the affected joints. Unfortunately, a large proportion of RA patients fail to respond adequately to current treatments. Here, repurposing hemin and its ultra-long-acting formulation were explored for the effective treatment of RA in animal models. We provided evidence that hemin prevented the onset and ameliorated the clinical course of RA. Notably, hemin treatment rescued the dysregulated gene expression in animal models of RA, resulting in attenuation of Th1/Th17 cell-mediated responses and proinflammatory cytokines. Moreover, we further formulated hemin into the in-situ forming implant, and a single injection of the ultra-long-acting hemin exerted potent disease-modifying effects for at least six weeks with a remarkable dose reduction. Taken together, given the potent anti-inflammatory and immunosuppressive effects, the once-monthly hemin injection holds promise for rapid clinical translation, and represents a potential strategy to treat RA and possibly other autoimmune diseases.